A finite-discrete element model for dry stone masonry structures strengthened with steel clamps and bolts. (1st May 2015) - Smoljanović, Hrvoje; Nikolić, Željana; Živaljić, Nikolina
Highlights: A new numerical model of steel clamps and bolts has been developed. The model was implemented in computer programme based on FEM/DEM method. The application was shown on dry stone masonry structures with clamps and bolts. The model was used for the estimation of the seismic resistance of the structures. Abstract: This paper presents a new robust finite-discrete element numerical model for analysis and prediction of the collapse of dry stone masonry structures strengthened with steel clamps and bolts. The model includes fracture and fragmentation of the blocks as well as a cyclic behaviour, yielding, stiffness degradation, failure and the influence of pulling out of the clamps and the bolts from the stone block. The developed model can be used for the estimation of the seismic resistance of historical dry stone masonry structures reinforced with steel clamps and steel bolts, which is very important for the structures classified as cultural heritage.